Use of silicate amendments on improvement of the quality and nutrition of the potato crop, variety 'Diacol Capiro' - David Fernando Torres-Hernández; Elberth Hernando Pinzón-Sandoval; Helber Enrique Balaguera-López; Amanda Silva-Parra; Pedro Jose Almanza-Merchán (Revista de Ciencias Agrícolas, 2024)
Potato (Solanum tuberosum L.) is one of the most important agricultural products in cold-climate areas of the world. However, the soils intended for potato production in tropical zones such as Colombia have low availability of essential elements, such as phosphorus, calcium, magnesium, and beneficial elements such as silicon. The general objective was to evaluate the application of increasing doses of three silicate amendments on the dynamics of accumulation of phosphorus, calcium, magnesium, and silicon in leaf tissue and their influence on the quality and production of 'Diacol Capiro' potato tubers under the conditions of Soracá municipality, Boyacá, Colombia. Two production cycles were evaluated, with a completely randomized design and ten treatments in each cycle. It was observed that the application of double calcium and magnesium silicate at a dose of 900 kg ha-1 as a crop management practice resulted in an increase in the accumulation of macronutrients such as P, Ca, and Mg by 63.1, 32.4, and 51.1%, respectively, and a 100% increase in silicon accumulation as a beneficial element; this was reflected in a 46% increase in total yield, with a higher production of first-quality tubers and a significant increase in dry matter and specific gravity compared to the application of conventional fertilization sources. Therefore, silicate fertilizers are an important alternative to improve quality and production through a better dynamic of accumulation of essential and beneficial nutrients in potato-producing areas in Colombia.